Respuestas

2013-11-12T03:08:46+01:00
01 xy2 - y2w = y2 (x - w) 5xy2 02 - 15 años = 5xy (y - 3) 03 24a3b2 - 12a3b3 = 12a3b2 (2 - b) 04 4xy - 8xy2 - 12xy3 4xy = (1 + 2y - 3y2) 05 16a4b5 - 20a3b2 - 24a2b6 = 4a2b4 (4A2B - 5a + 6b2) 06 xa + 2 - 3XA + 3 - 5XA = xa (x2 + 3x3 + 5) 07 36x2ayb - 24xa 1YB + 1 + 12xay2b = 12xayb (3XA - 2xy + YB) x 08 (a + 7) - 5 (a + 7) = (a + 7) (x - 5) 09 2x (a - 1) - 3a (a - 1) = (a - 1) (2x - 3a) x 10 (a + 9) - un - 9 = (a + 9) (x - 1) 11 - x - y + a (x + y) = (x + y) (a - 1) 12 ( a + 5) (a + 1) - 2 (a + 1) = (a + 1) (a + 3) 13 (a + b - 2) (a2 + 2) - a2 - 2 = (a2 + 2) (a + b - 3) 14 (3x2 + 8) (x + y - z) - (3x2 + 8) - (x + y - 4) (3x2 + 8) = (3x2 + 8) (3 - z) 15 xm - ym + xn - yn = (x - y) (m + n) 16 a2x2 - 8bx2 + a2y2 - 8by2 = (x2 + y2) (a2 - 8b) 17 1 + a + 8ab 8b + = (a + 1) (8b + 1) 18 6ax - 2por - 2bx - 12a + 6AY + 4b = (6a - 2b) (x + y - 2) 19 a2b3 - m5 + a2b3x2 - m5 x2 - 3a2b3x + 3m5x = (a2b3 - m5 ) (1 - 3x + x2) 20 (x + 3) (x + 2) (x + 5) + (x + 2) (x + 5) + (x + 5) = (x + 5) (x + 3) 2